ANALISIS PENGARUH TINGKAT SUKU BUNGA, NON PERFORMING LOAN, DAN LOAN DEPOSIT RATIO TERHADAP PENYALURAN KREDIT UMKM Studi Kasus Bank Umum di Indonesia Periode 2008-2017 - Aldhella Arcy Desya; Lorentino Togar Laut; Yustirania Septiani (Universitas Tidar, 2019)
The purpose of this study was to determine how much influence the variable amount of interest rate, non performing loan and loan deposit ratio either simultaneous or partially affect the variable SME’s lending. The data collected is secondary data obtained from commercial banks performance report year 2008-2017. Data collection technique obtained from Indonesian banking statistics for 15 years from the Bank Indonesia. In this study using α of 5% and techniques of multiple linear regression data analysis, statistical tests, and classical assumption. The survey results revealed detachment from the classical assumption, then the estimation results of regression and t test showed that the interest rate during the year 2008-2017 have no significant effect on SME’s lending. However, t test of non performing loan and loan deposit ratio during the year 2080-2017 showed a significant effect SME’s lending. simultaneously shows that the interest rate, non permorming loan and loan deposit ratio have a significant effect on SME’s lending. Keywords: interest rate, non performing loan, and SME’s lending